ACCREDITATION OF THE FACULTY OF MEDICINE UNIVERSITY OF GEZIRA (FMUG), PILOT STUDY - Mirghani, Omer Ahmed; El Sanousi, Mohamed; Abdulla, Mohamed El Hassan; Mohamed Osman, Osman Taha; Habour, Ali Babiker; Mohamed Ahmed, Sayed; Mehamadan, Ahmed Abdulla; El Toum, Hashim; Abdul Hafeez, Abdul Rahman; El Mukhtar, Mohamed (Gezira Journal of Health Sciences, 2005)
The Faculty of Medicine University of Khartoum was founded in 1924 and has graduated the majority of doctors in the Sudan. In recent years the government invested heavily in higher education and 26 new medical schools have been established and are now functioning and graduating doctors. Those new schools adopted different models of curricula, however most of them benefited from the Gezira medical school experience and hence their curricula are innovative. The large number of schools and the diversity in their curricular models fueled interest in the Sudan General Medical Council and the Ministry of Higher Education to establish a national mechanism for evaluating those schools and ensuring the society that they graduate doctors with optimum standard.